Maintaining Marine Ecosystem to Realize Halal Supply Chain from The MaqÄsid al-SharÄ«”˜ah Perspective - Hakim, Imamul; Ridwan, Muhtadi; Zenrif, Muchammad Fauzan; Saiban, Kasuwi (IAIN Ponorogo, 2024)
This article aims to examine the importance of preserving marine ecosystems from the perspective of maqÄsid al-sharÄ«’ah as an effort to realize a good food product supply chain, and to maintain and realize halal and tayyib (clean and pure) food products. The research method approach used in this article is a literature study or literature review. Sources are collected from books and various research articles on pollution of the marine environment and its consequences for human health that have been carried out by previous researchers, then studied from the perspective of maqÄsid al-sharÄ«’ah. The findings in this study show that the problem of damage to marine ecosystems due to pollution is a big problem that must be resolved, because of the impact caused not only on the environment but also on human health problems as a result of consuming marine biota exposed to waste, especially heavy metals. While preserving the ecosystem is part of maqÄsid al-sharÄ«’ah. Therefore, in realizing halal products that are tayyib, serious attention is needed on supply chain sources. The results of this research can contribute to thinking and decision-making regarding the importance of preserving the environment in realizing a good source of food supply.